Unveiling revisit intentions: exploring factors impacting Singaporean tourists in halal food restaurants - Azhar, Anis Syuhada; Mohd, Nur Shuhadah; Mohamad, Mohamad Amiruddin; Md Sawari, Siti Salwa; Najimudin, Muhammad Fadhlullah (Springer Nature Singapore Pte Ltd., 2024)
The Halal industry is expansive and continually evolving, presenting a range of challenges in the global arena. Particularly, the increased competition among Singaporean tourists visiting Malaysia underscores the importance of comprehending factors influencing their likelihood of returning. As Islamic value concerns the reinforcement of service provider’s commitment to deliver the best effort, the factor shaping tourists’ loyalty and desire to revisit Islamic food services, particularly Halal restaurants, is still vague. Therefore, this study delves into the impact of services, specifically service quality, physical environment, and price perception, on the intentions of Singaporean tourists to revisit Halal food restaurants in Malaysia. Employing a quantitative research approach, the study engaged 75 respondents through online survey distribution. The results reveal that tourists’ decisions to revisit Halal restaurants are primarily shaped by service quality and price perception, rather than the physical ambience of the restaurant. These findings shed light on the determinants of tourists revisiting Halal eateries and contribute to the existing body of research in this domain.